Prognostic significance of X‐linked inhibitor of apoptosis protein in solid tumors: A systematic review and meta‐analysis. Issue 10 (7th March 2019) - Li, Shimeng; Pan, Baoxiang; Li, Lihong; Shi, Bo; Xie, Feng; He, Chengyan
Abstract: X‐linked inhibitor of apoptosis protein (XIAP) is aberrantly expressed in solid tumors. Considering conflicting data, we conducted this meta‐analysis to investigate its prognostic role. Electronic databases were searched to collect studies about associations between XIAP expressions and survival outcomes. Hazard ratio (HR), odds ratio (OR), and 95% confidence interval (CI) were utilized as effect size estimates. A total of 3, 794 patients from 21 published studies were included. The results revealed that high XIAP expressions correlated with age (OR = 2.02; 95% CI, 1.07–3.84), lymph node metastasis (OR = 1.69; 95% CI, 1.02–2.77), histological grade (OR = 2.04; 95% CI, 1.01–4.11), and tumor stage (OR = 2.18; 95% CI, 1.20–3.96). The combined HR revealed that high XIAP expressions associated with poor overall survival (OS) (HR = 1.60; 95% CI, 1.22–2.10). Our study suggested high XIAP expressions may be indicative of poor prognosis in solid tumors. Abstract : The results revealed that high X‐linked inhibitor of apoptosis protein (XIAP) expressions correlated with age, lymph node metastasis, histological grade, and tumor stage. Our study suggested high XIAP expressions may be indicative of poor prognosis in solid tumors.